The expressive powers of law : theories and limits - McAdams, Richard H. (Harvard University Press, 2015)
Why do people obey the law? Law deters crime by specifying sanctions, and because people internalize its authority. But Richard McAdams says law also generates compliance through its expressive power to coordinate behavior (traffic laws) and inform beliefs (smoking bans)--that is, simply by what it says rather than what it sanctions.